Kajian Komposisi Bahan Tambahan Pangan Pada Produk Daging Ayam Olahan Komersial - Lalu Danu Prima Arzani; Qabul Dinanta Utama (Food Scientia : Journal of Food Science and Technology, 2023)
The aim of this research is to identify the composition of food additives present in commercial processed chicken meat products based on regulations in Indonesia. The evaluated samples consisted of 47 various commercial processed chicken meat products. The observed food additives included flavor enhancers, emulsifiers, preservatives, stabilizers, antioxidants, acidity regulators, leavening agents, and colorants. The food additives used in chicken meatball products were flavor enhancers (42.86%), emulsifiers (4.76%), stabilizers (23.81%), and acidity regulators (28.57%). In chicken sausage products, flavor enhancers (23%), stabilizers (23%), antioxidants (17%), emulsifiers (3%), preservatives (15%), acidity regulators (12%), and colorants (7%) were found. In chicken dumpling products, acidity regulators (40%), flavor enhancers (20%), stabilizers (20%), preservatives (13%), and colorants (7%) were identified. In chicken nugget products, colorants (26%), flavor enhancers (22%), stabilizers (18%), antioxidants (11%), emulsifiers (11%), preservatives (7%), leavening agents (2%), and acidity regulators (2%) were present. In the category of processed chicken meat products (08.2.3.), stabilizers (21.54%), flavor enhancers (33.85%), colorants (18.46%), preservatives (10.77%), antioxidants (7.69%), and leavening agents (7.69%) were detected. The usage of food additives and the consumption of products containing these additives, particularly those with carcinogenic risks, need to be regulated and addressed by the government and consumers alike. Future research efforts to discover safer alternatives for these food additives are highly recommended.